2022
DOI: 10.1093/plphys/kiac020
|View full text |Cite
|
Sign up to set email alerts
|

CamelliA-based simultaneous imaging of Ca2+ dynamics in subcellular compartments

Abstract: As a universal second messenger, calcium (Ca2+) transmits specific cellular signals via a spatiotemporal signature generated from its extracellular source and internal stores. Our knowledge of the mechanisms underlying the generation of a Ca2+ signature is hampered by limited tools for simultaneously monitoring dynamic Ca2+ levels in multiple subcellular compartments. To overcome the limitation and to further improve spatiotemporal resolutions, we have assembled a molecular toolset (CamelliA lines) in Arabidop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 120 publications
(189 reference statements)
0
4
0
Order By: Relevance
“…However, substantial oscillations of cytosolic pH in pollen tubes, guard cells or mesophyll cells had no visible effects on cytosolic R-GECO1 (Li et al, 2021). Measurements of cytosolic Ca 2+ during pH oscillations in Arabidopsis pollen tubes showed that jR-GECO1a gave similar results to the pH-insensitive Ca 2+ sensor yellow cameleon YC3.6 (Guo et al, 2022). R-GECO1 based Ca 2+ indicators have previously been used to measure Ca 2+ dynamics in organelles, such as the mitochondria of animal cells, although they exhibited some sensitivity to large increases in pH induced by 30 mM NH4Cl (Hou et al, 2017;Kanemaru et al, 2020).…”
Section: Introductionmentioning
confidence: 79%
“…However, substantial oscillations of cytosolic pH in pollen tubes, guard cells or mesophyll cells had no visible effects on cytosolic R-GECO1 (Li et al, 2021). Measurements of cytosolic Ca 2+ during pH oscillations in Arabidopsis pollen tubes showed that jR-GECO1a gave similar results to the pH-insensitive Ca 2+ sensor yellow cameleon YC3.6 (Guo et al, 2022). R-GECO1 based Ca 2+ indicators have previously been used to measure Ca 2+ dynamics in organelles, such as the mitochondria of animal cells, although they exhibited some sensitivity to large increases in pH induced by 30 mM NH4Cl (Hou et al, 2017;Kanemaru et al, 2020).…”
Section: Introductionmentioning
confidence: 79%
“…Primers used for amplification and assembly of these constructs are listed in Supplemental Table S3 . The ERN1 native promoter–driven complementation construct (ERN1pro::ERN1-mEGFP) was generated in a single reaction, using the NEBuilder HiFi DNA Assembly Master Mix (NEB, E2621), to assemble 3 fragments into a modified pCAMBIA1300-MCS vector that lacks a promoter ( Guo et al 2022 ) ( Supplemental Table S3 ). The promoter and coding sequence of ERN1 without the stop codon were amplified from genomic DNA of WT Arabidopsis plants.…”
Section: Methodsmentioning
confidence: 99%
“…Wild-type (Col-0) expressing GCaMP6 (ref. 44) driven by the pollenspecific LAT52 promoter 48,49,72 ] i in pollen grains were carried out as described in previous studies with modifications 6,25,56,72,[78][79][80][81][82][83] . Pollen grains from freshly opened mature (stage 12-13) flowers were dispersed on the solid germination medium with indicated osmolarity.…”
Section: Imaging Of [Ca 2+ ] I In Pollen Grainsmentioning
confidence: 99%